Substitusi Tepung Garut (Maranta Arundinaceae Linn.) Dalam Pembuatan Bakpao - Ira Handayani; Izzul Azmi Shofura (Akademi Kesejahteraan Sosial Ibu Kartini Semarang, 2022)
Bakpao which is processed with local food ingredients such as arrowroot tubers can increase the economic value and people's consumption power of local food ingredients. Arrowroot tubers can be used as a source of carbohydrates to replace rice and wheat flour. The objectives of this study are (1) to determine the acceptance of the community towards the most preferred rice balls with arrowroot flour substitution. (2) to determine the composition of the ingredients used in the manufacture of rice balls with the most preferred substitution of arrowroot flour. (3) to determine the process of making buns with the most preferred substitution of arrowroot flour. The methods and data analysis used in this research are library, experimental, documentation, sensory test and descriptive data analysis methods. The percentage of arrowroot flour substitution in the manufacture of arrowroot flour substitution buns was 20%, 30%, and 40% of the weight of wheat flour. The overall assessment using the highest ranking of the three samples with the criteria of shape, taste, color, texture, and aroma is the bakpao sample with the substitution of arrowroot flour by 20%.